Potential use of angiotensin receptor blockers in skin pathologies - Keshvad Hedayatyanfard; Azadeh Khalili; Hosein Karim; Soren Nooraei; Ehsan Khosravi; Nazgol Sadat Haddadi; Ahmad Reza Dehpour; Gholamreza Bayat (Iranian Journal of Basic Medical Sciences, 2023)
Renin-angiotensin system (RAS) components such as angiotensin II, angiotensin receptors (AT1R and AT2R), and angiotensin-converting enzyme (ACE) are expressed in different cell types of the skin. Through AT1R, angiotensin II increases proinflammatory cytokines contributing to fibrosis, angiogenesis, proliferation, and migration of immune cells to the skin. In contrast, AT2R suppresses the effects mentioned above. Many studies show that angiotensin receptor blockers (ARBs) and angiotensin-converting enzymes (ACEi) reduce the proinflammatory cytokines and fibrogenic factors including transforming growth factor β (TGF-β), Connective tissue growth factor (CTGF), and IL-6. This review article provides a detailed research study on the implications of ARBs in wound healing, hypertrophic scar, and keloids. We further discuss the therapeutic potentials of ARBs in autoimmune and autoinflammatory skin diseases and cancer, given their anti-fibrotic and anti-inflammatory effects.